PENGARUH PAD, DAU, DAK TERHADAP PERTUMBUHAN EKONOMI DAN KEMISKINAN PADA KABUPATEN/KOTA DI INDONESIA - Adhi Prasetyo; Ade Nurul Aida (Pusat Kajian Anggaran, 2017)
This study investigate the effect of Local Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK) to economic growth and poverty at district/city in Indonesia for 2012-2014. Research using the method of path analysis with secondary data in the form of a panel consisting of 33 provinces include 441 district/city in Indonesia were sourced from the Directorate General of Financial Equalization (DJPK) and the BPS-Statistics Indonesia. Results shows that the PAD and DAU effect on economic growth in each district/city area. Otherwise DAK has no effect against economic growth. In addition, this analysis also showed that PAD, and DAU effect on poverty, but DAK had no effect against poverty at district/city in Indonesia. While economic growth would also have an effect on poverty. From the analysis also looks that indirectly PAD, and DAU to decrease poverty through increased economic growth.